Pascal-Interpolation-Based Noninteger Delay Filter and Low-Complexity Realization - P. Soontornwong; S. Chivapreecha (My University, 2015)
This paper proposes a new method for designing the polynomial-interpolation-type noninteger-delay filter with a new structure formulation.Since the design formulation and the new realization structure are based on the discrete Pascal transform (DPT) and Pascal interpolation, we call the resulting filter Pascal noninteger-delay filter.The kth-order Pascal polynomial is used to pass through the given (k + 1) data points in achieving the kth-order Pascal filter.The Pascal noninteger-delay filter is a realtime filter that consists of two sections, which can be realized into the front-section and the back-section.The frontsection contains multiplication-free digital filters, and the number of multiplications in the back-section just linearly increases as order becomes high.Since the new Pascal filter has low complexity and structure can adjust noninteger delay online, it is more suited for fast delay tuning.Consequently, the polynomial-interpolation-type delay filter can be achieved by using the Pascal approach with high efficiency and low-complexity structure.
Keywords: Realization (probability); Pascal (unit); Interpolation; Digital Filter Design and Implementation